Levodopa and Huntington's chorea. Issue 10 (October 1976) - Loeb, C.; Roccatagliata, G.; Medica, G. La; Abbruzzese, G.; Albano, C.
Abstract : Two patients with Huntington's chorea are reported whose psychiatric and neurological symptoms greatly improved after treatment with L-dopa. In both cases the basal values of CSF HVA were markedly decreased, being increased by the treatment with L-dopa.